2006
DOI: 10.1021/ja062417w
|View full text |Cite
|
Sign up to set email alerts
|

Facile Functionalization of a Metal Carbon Bond by O-Atom Transfer

Abstract: A key challenge to developing selective, low-temperature hydrocarbon oxidation catalysts based on the CH activation reaction is integration with a compatible functionalization reaction. 1,2 We recently reported a CH activation reaction (Figure 1) with an alkoxo complex, M-OR, that simultaneously generates a functionalized product, ROH, and a metal alkyl, M-R, where M is Ir(III). 3a,b As shown in Figure 1, a catalytic cycle for the conversion of RH to ROH could be possible by regeneration of M-OR from M-R with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 13 publications
3
74
0
Order By: Relevance
“…At ambient temperatures the dioxophenyl complex undergoes phenyl-to-oxo migration. [133] With [136] Mechanistic studies show that the reaction pathway for the MTO system does not likely occur by an oxo-insertion mechanism. A mechanism similar to the classic Baeyer-Villiger [137] organic reaction has been proposed (Scheme 23).…”
Section: Cào Bond Formationmentioning
confidence: 99%
“…At ambient temperatures the dioxophenyl complex undergoes phenyl-to-oxo migration. [133] With [136] Mechanistic studies show that the reaction pathway for the MTO system does not likely occur by an oxo-insertion mechanism. A mechanism similar to the classic Baeyer-Villiger [137] organic reaction has been proposed (Scheme 23).…”
Section: Cào Bond Formationmentioning
confidence: 99%
“…20 More recently, Periana et al have reported the reaction of methylrheniumtrioxo with external oxidants (e.g., hydrogen peroxide, pyridine-N-oxide, periodate, and iodosyl benzene) to form Re(OMe)O 3 . 21 Importantly, these transformations occur relatively rapidly at room temperature, and preliminary mechanistic studies indicate that the oxygen atom in the final methoxo ligand does not originate from a Re-oxo moiety. A mechanism similar to the classic Baeyer-Villiger organic reaction 54 has been proposed.…”
Section: Summary Conclusion and Prospectusmentioning
confidence: 99%
“…20,21 For the present models we have kept the d-electron count fixed at six, which has necessitated variation of the overall charge. While the precise relationship between the kinetics and thermodynamics of these transformations Vis-à-Vis d-electron counts and metal formal oxidation states is not entirely understood, it is reasonable to expect that a marriage of these two transformations may require a catalyst that satisfies both requirements (such as Co III , Pt IV , etc.).…”
Section: Summary Conclusion and Prospectusmentioning
confidence: 99%
“…Facile oxy-functionalization reactions of nucleophilic M δ+ -R δ− complexes are rare, [1][2][3][4][5] although functionalizations are well-known for M δ− -R δ+ intermediates of more electronegative metals. [6][7][8] Some of us reported recently both theory and experiments on the reaction of methylrhenium trioxide (CH 3 -ReO 3 , MTO) with oxidants (H 2 O 2 , PhIO, and IO 4 − ) in the aqueous phase.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Some of us reported recently both theory and experiments on the reaction of methylrhenium trioxide (CH 3 -ReO 3 , MTO) with oxidants (H 2 O 2 , PhIO, and IO 4 − ) in the aqueous phase. 2,9 We concluded that the reaction proceeds through a Baeyer-Villiger (BV) type transition state 9 leading to formation of methanol in high yields (>80%). More recently, we studied the oxidation of 2,4,6-trimethylphenylrhenium trioxide (Mes-ReO 3 , MesTO) in similar conditions.…”
Section: Introductionmentioning
confidence: 99%